2019
DOI: 10.3847/1538-4357/ab3723
|View full text |Cite
|
Sign up to set email alerts
|

Resolved and Integrated Stellar Masses in the SDSS-iv/MaNGA Survey. I. PCA Spectral Fitting and Stellar Mass-to-light Ratio Estimates

Abstract: We present a method of fitting optical spectra of galaxies using a basis set of six vectors obtained from principal component analysis (PCA) of a library of synthetic spectra of 40000 star formation histories (SFHs). Using this library, we provide estimates of resolved effective stellar mass-to-light ratio (Υ * ) for thousands of galaxies from the SDSS-IV/MaNGA integral-field spectroscopic survey. Using a testing framework built on additional synthetic SFHs, we show that the estimates of log Υ * i are reliable… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 125 publications
0
11
0
Order By: Relevance
“…The stellar content of a galaxy is therefore a valuable diagnostic for its integrated star formation and chemical enrichment history. For this work, we take the estimates of stellar mass per spaxel provided by Pace et al (2019aPace et al ( , 2019b. With this method, individual spectra are fitted using a basis set of six vectors, found using principal Figure 1.…”
Section: Stellar Mass Surface Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…The stellar content of a galaxy is therefore a valuable diagnostic for its integrated star formation and chemical enrichment history. For this work, we take the estimates of stellar mass per spaxel provided by Pace et al (2019aPace et al ( , 2019b. With this method, individual spectra are fitted using a basis set of six vectors, found using principal Figure 1.…”
Section: Stellar Mass Surface Densitymentioning
confidence: 99%
“…Dust attenuation is taken into account using a two-component model following Charlot & Fall (2000), whereby light from the younger component of the stellar population experiences a different degree of extinction than the light from the older stellar populations. Pace et al (2019a) showed that this technique provides statistically robust estimates of the stellar mass-tolight ratio across a wide range of S/Ns, star formation histories, and metallicities, with random uncertainties typically 0.1 dex or less for spectra with S/N>2.…”
Section: Stellar Mass Surface Densitymentioning
confidence: 99%
“…In recent years, full spectral fitting of integrated light spectra to model spectra has opened a new window to study in detail the physical, chemical and evolutionary phases of galaxy stellar populations (e.g. Pérez et al 2013;Pace et al 2019;Boardman et al 2020). Some of the most widely used spectral fitting software for this technique are FIREFLY (Wilkinson et al 2017), STECKMAP (Ocvirk et al 2006), VESPA (Tojeiro 2007), pPXF (Cappellari et al 2009), ULySS (Koleva et al 2009), STARLIGHT (Cid Fernandes et al 2011), andPipe3D (Sánchez et al 2016a,b).…”
Section: Introductionmentioning
confidence: 99%
“…This means that the complicated spectral features including more than 30 lines are controlled by several bases represented by the PCs. This advantage itself is a well-known benefit to use the PCA in general as a dimensionality reduction method (e.g., Galaz & de Lapparent 1998;Ronen et al 1999;Wang et al 2011;Pace et al 2019;Portillo et al 2020, among many others), but all these previous applications were on integrated 1-d spectra with sufficiently large number of n, namely, not HDLSS data. We stress that the analysis in this work is substantially different from these works: the current method is able to be applied to a spectral map which is a typical HDLSS dataset and traditional PCA would not have worked due to the huge noise sphere, as mentioned in Section 2.…”
Section: Distribution Of the Contribution Of Pcsmentioning
confidence: 99%